Increased Genomic Integrity of an Improved Protein-Based Mouse Induced Pluripotent Stem Cell Method Compared With Current Viral-Induced Strategies. (24th April 2014) - Park, Hansoo; Kim, Dohoon; Kim, Chun-Hyung; Mills, Ryan E.; Chang, Mi-Yoon; Iskow, Rebecca Cheryl; Ko, Sanghyeok; Moon, Jung-Il; Choi, Hyun Woo; Man Yoo, Paulo Sng; Do, Jeong Tae; Han, Min-Joon; et al.
Abstract : This study identified an increased copy number variant (CNV) content in lenti-miPSCs and retro-miPSCs (29∼53 CNVs) compared with p -miPSCs (9∼10 CNVs), indicating that this improved protein-based reprogramming method maintains genomic integrity better than current viral reprogramming methods. Thus, this study demonstrates that reprogramming methods significantly influence the genomic integrity of resulting induced pluripotent stem cells. Abstract: It has recently been shown that genomic integrity (with respect to copy number variants [CNVs]) is compromised in human induced pluripotent stem cells (iPSCs) generated by viral-based ectopic expression of specific transcription factors (e.g., Oct4, Sox2, Klf4, and c-Myc). However, it is unclear how different methods for iPSC generation compare with one another with respect to CNV formation. Because array-based methods remain the gold standard for detecting unbalanced structural variants (i.e., CNVs), we have used this approach to comprehensively identify CNVs in iPSC as a proxy for determining whether our modified protein-based method minimizes genomic instability compared with retro- and lentiviral methods. In this study, we established an improved method for protein reprogramming by using partially purified reprogramming proteins, resulting in more efficient generation of iPSCs from C57/BL6J mouse hepatocytes than using protein extracts. We also developed a robust and unbiased 1 M custom array CGH platform to identify novel CNVs and previously described hot spots for CNV formation, allowing us to detect CNVs down to the size of 1.9 kb. The genomic integrity of these protein-based mouse iPSCs ( p -miPSCs) was compared with miPSCs developed from viral-based strategies (i.e., retroviral: retro-miPSCs or lentiviral: lenti-miPSCs). We identified an increased CNV content in lenti-miPSCs and retro-miPSCs (29∼53 CNVs) compared with p -miPSCs (9∼10 CNVs), indicating that our improved protein-based reprogramming method maintains genomic integrity better than current viral reprogramming methods. Thus, our study, for the first time to our knowledge, demonstrates that reprogramming methods significantly influence the genomic integrity of resulting iPSCs.